Supplementation With Lycium barbarum Polysaccharides Reduce Obesity in High-Fat Diet-Fed Mice by Modulation of Gut Microbiota - Yang, Mei; Yin, Yexin; Wang, Fang; Zhang, Haihan; Ma, Xiaokang; Yin, Yulong; Tan, Bie; Chen, Jiashun (Frontiers in Microbiology, 2021)
Lycium barbarum polysaccharides (LBPs) have been proved to prevent obesity and modulate gut microbiota. However, the underlying mechanisms of LBPs regulating lipid metabolism remain entirely unclear. Therefore, the purpose of this study was to determine whether LBPs are able to modulate the gut microbiota to prevent obesity. The results showed that oral administration of LBPs alleviated dyslipidaemia by decreasing the serum levels of total triglycerides (TG), total cholesterol (TC), and low-density lipoprotein-cholesterol (LDL-C), and elevating the high-density lipoprotein cholesterol (HDL-C) in obese mice. Furthermore, LBPs treatment decreased the number and size of adipocytes in epididymal adipose tissues and down-regulated the expression of adipogenesis related genes, including acetyl-CoA carboxylase 1(ACC-1), fatty acid synthase (FAS), stearoyl-CoA desaturase 1 (SCD1), sterol regulatory element binding protein-1c (SREBP-1C), peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer-binding protein α (C/EBPα). 16S rRNA gene sequencing analysis showed that LBPs increased the diversity of bacteria, reduced the Firmicutes/Bacteroidetes ratio, improved the gut dysbiosis induced by a high-fat diet, for example, LBPs increased the production of short-chain fatty acids (SCFAs)-producing bacteria Marvinbryantia, Lachnospiraceae_NK4A136_group and Butyricicoccus. LBPs treatment also increased the content of fecal SCFAs, including butyric acid. These findings illustrate that LBPs might be developed to a potential prebiotic to improve lipid metabolism and intestinal diseases.